A qualidade ambiental urbana no bairro Alfredo Freire Uberaba / MG : o desafio da análise e representação - Teobaldo Neto, Aristoteles (2008)
The urban growth, most of the time, is not followed by an adjusted infrastructure that guarantees a healthful environment and a proper life quality. The urbanization and industrialization increasing process has provoked significant alterations in the environment. It has been modifying some vital supplements quality , such as: pure and cool air, drinking water, food, leisure spaces, amongst others. A quarter in Uberaba MG, symbolizes this process: Alfredo Freire. It is located next to an Industrial District and has the environmental quality affected by the residues generated in the neighboring industrial activities. It was arisen as problematic issues which guides this research: Why to construct a quarter segregated from the city (at that time) and next to an Industrial District? Which is its inhabitants perception in relation to the quarter environmental quality? From this, it was defined as general objective: to elaborate and analyze the urban perception map of Alfredo Freire quarter environmental quality and as specific objective: to understand the city production and reproduction processes; to outline some general characteristics of the quarter inhabitants social-economic profile; to identify and to establish the ambient perception of the inhabitants in relation to some ambient quality pointers; elaborate the maps of each pointer; interpolate the maps, elaborate and analyze the final map of Urban Environmental Quality (QAU). In chapter 1 a historical incursion in the issue studied in this research is developed, searching to determine the causes and understand the processes that mix the miserable social-ambient situation. It is introduced the discussion concerning QAU evaluation concepts and methods and life quality. In chapter 2 the methodology, the operational procedures and the materials used in the research are presented. Chapter 3 presents the history of the quarter and the inhabitant profile. Initially, it is done a geographic-historical characterization of the study area. In this context it will be clear how the problematic environmental issue is in the quarter genesis. In chapter 4, are presented the results directly related to the four defined pointers of the environmental quality in the specific objectives. Such results are presented in the form of maps, graphs and tables. It is demonstrated how QAU s synthesis map was elaborated, by the criterion of the simple average. Some consideration about this method limitation are explained and one second alternative is presented: the interpolation method. So that, this is the closest to the reality. It is argued, also, how the technologies related to the geo-processing can be useful and efficient in the studied phenomenon analysis and QAU representation. Finally, some proposals are presented as urgent measures with the objective to minimize the environment impacts and improve the life and ambient quality of Alfredo Freire quarter inhabitants in Uberaba-MG.